Evaluation of psychological impact, depression, and anxiety among pregnant women during the COVID‐19 pandemic in Lahore, Pakistan. Issue 3 (17th October 2020) - Shahid, Ayesha; Javed, Amna; Rehman, Saba; Tariq, Rukiya; Ikram, Muhammad; Suhail, Muhammad
Abstract : Concerns about vulnerability to COVID‐19 and vertical transmission of the disease led to increased incidence of psychological distress, depression, anxiety, and sleep disturbance among pregnant women in Lahore, Pakistan.